Engineered RBCs Encapsulating Antigen Induce Multi-Modal Antigen-Specific Tolerance and Protect Against Type 1 Diabetes - Raposo, Colin J.; Cserny, Judith D.; Serena, Gloria; Chow, Jonathan N.; Cho, Patricia; Liu, Hanyang; Kotler, David; Sharei, Armon; Bernstein, Howard; John, Shinu (Frontiers in Immunology, 2022)
Antigen-specific therapies that suppress autoreactive T cells without inducing systemic immunosuppression are a much-needed treatment for autoimmune diseases, yet effective strategies remain elusive. We describe a microfluidic Cell Squeeze® technology to engineer red blood cells (RBCs) encapsulating antigens to generate tolerizing antigen carriers (TACs). TACs exploit the natural route of RBC clearance enabling tolerogenic presentation of antigens. TAC treatment led to antigen-specific T cell tolerance towards exogenous and autoantigens in immunization and adoptive transfer mouse models of type 1 diabetes (T1D), respectively. Notably, in several accelerated models of T1D, TACs prevented hyperglycemia by blunting effector functions of pathogenic T cells, particularly in the pancreas. Mechanistically, TACs led to impaired trafficking of diabetogenic T cells to the pancreas, induced deletion of autoreactive CD8 T cells and expanded antigen specific Tregs that exerted bystander suppression. Our results highlight TACs as a novel approach for reinstating durable immune tolerance in autoimmune patients.